Preface - PĘCHERSKI, Ryszard (Engineering Transactions, 2014)
Three years have passed since we started a fruitful cooperation editing the Quarterly Journal ENGINEERING TRANSACTIONS together with the National Engineering School of Metz – ENIM, France. I would like to express thanks and gratitude for the permanent support and interest in this undertaking from the side of the director of ENIM – professor Pierre Chevrier as well as for the efforts of the co-editor professor Alexis Rusinek. Without their contribution the editing of the twelve issues of the Journal with scientific papers from many countries would be not possible. In this way our Quarterly, founded in 1952 by Witold Nowacki, Wacław Olszak, and Witold Wierzbicki and appearing since 1953, has been set on a new path of development in its 60 year history. Starting with this issue our cooperation has been enriched by a third partner – one of the best and most dynamically developing technical universities in Poland: the Poznan University of Technology. Professor Tomasz Łodygowski – the Rector of PUT declared the intention of active cooperation in editing our Quarterly. Our partners in Poznań closed a local scientific journal: Journal of Civil and Environmental Engineering of its own tradition of editing valuable scientific papers and technical reports for 12 years to concentrate on publishing in ENGINEERING TRANSACTIONS. Having in mind a large number of young scientists working at the PUT as well as predicting the snowball effect regarding other technical universities in Poland, such a decision will enhance the editorial situation of our Quarterly. Ryszard Pęcherski Editor